Measuring Company Performance Based on Balanced Scorecard and Determination of Analytical Hierarchy Process Priority in CV. Pujon Ramie Lestari - Meylinda Zulfah; M. Jihadi; Dewi Nurjannah (Universitas Muhammadiyah Malang, 2022)
The Balanced Scorecard has been widely applied to large and small companies in measuring company performance from financial and non-financial aspects, so the purpose of the research is to measure company performance as a whole using the Balanced Scorecard as a performance measurement on the CV. Pujon Ramie Lestari will be combined with prioritization using the Analytical Hierarchy Process. Measurement of the priority weights of CV. Pujon Ramie Lestari will be measured using the AHP method. Data collection in this research was carried out by interviews and questionnaires which would be processed using the AHP method. The results show that the perspective that has the highest weight with the most important priority is the internal business process perspective with good enough performance indications, the second priority is the customer perspective with good enough performance indications, the third priority is the learning and growth perspective with sufficient performance indications, and the last priority is the learning and growth perspective.